Demitologization of Local Culture as a Queue to Religious Radicalism: Nurcholish Madjid’sThoughts on Local Culture in Indonesia - Iswahyudi (Religion, Culture, and State Journal, 2021)
Nurcholis Madjid’s thoughts on local culture rarely become the concentration of researchers. Researchers are trapped in the general assumption that Nurcholish Madjid is a thinker of Islamic modernism in the grand flow of refinement of teachings as he admires Ibn Taymiyah. Therefore, his views on local culture that are critically appreciative are forgotten in their working papers. Nurcholis Madjid’s view of the local culture can be used as a bridge for the deradicalization of one’s religious understanding. This article, therefore, aims at first, finding Nurcholish Madjid’s views on local culture; secondly, looking for factors that affect Nurcholis Madjid’s thoughts about local culture and thirdly, finding the relevance of Nurcholish Madjid’s thoughts about local culture to the current condition of Indonesia. Through the critical analytical descriptive method, this articleconcluded three findings; First, local culture for Nurcholish Madjid is the cultural richness of a nation that gives colour to religious thought. For him, local culture must be demitologized. Second, Nurcholis Madjid’s thoughts about local culture are influenced by multi ideological education factors and a pluralist social environment. Third, the thought of Nurcholish Madjid provides a new perspective for radical understanding which is connected with the problem of religious and cultural relations.